2020
DOI: 10.1111/1744-1633.12436
|View full text |Cite
|
Sign up to set email alerts
|

Distant surgical teaching during COVID‐19 ‐ A pilot study on final year medical students

Abstract: Introduction Due to the COVID‐19 outbreak, all on‐site undergraduate medical teaching activities in Hong Kong have been suspended. A new web‐based surgical skills learning (WSSL) for basic surgical skills training that were normally taught face‐to‐face was developed. Methodology Basic surgical skills were taught with normal face‐to‐face tutorial to 30 final year medical students prior to the outbreak. The same group of students were invited to join the online WSSL using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 5 publications
1
75
0
3
Order By: Relevance
“…A significant number of published studies indicated that a major disadvantage of virtual teaching is technical difficulties [11,15,18,21,22,25,27,29,30,37,38,42,44]. On further analysis of the technical difficulties experienced by students, several different challenges to virtual teaching arose.…”
Section: Principal Weaknesses Of Virtual Teachingmentioning
confidence: 99%
“…A significant number of published studies indicated that a major disadvantage of virtual teaching is technical difficulties [11,15,18,21,22,25,27,29,30,37,38,42,44]. On further analysis of the technical difficulties experienced by students, several different challenges to virtual teaching arose.…”
Section: Principal Weaknesses Of Virtual Teachingmentioning
confidence: 99%
“…Especially the breakout rooms, in which participants can be divided into small groups for discussions or meetings for a certain period of time, make it possible to do justice to the current conditions and still maintain a high level of interaction. The experience of ETHZ corresponds with the experiences of other institutions [ 4 ], [ 5 ].…”
Section: Monitoring Of Covid-19 Placementsmentioning
confidence: 91%
“…In the news report, the attending doctor was able to answer the patient's queries and examine the wound closely using the commercially available videoconference software 19 . In the realm of surgical education, the University of Hong Kong has developed a new web‐based surgical skills learning (WSSL) for basic surgical skill training with promising feedback from a group of final year medical students 20 . In light of the aforesaid benefits, it is envisaged that telehealth will gain further momentum and become a new norm of interaction between healthcare professionals and patients.…”
Section: The Development Of Telehealth Surgical Practicementioning
confidence: 99%
“…19 In the realm of surgical education, the University of Hong Kong has developed a new web-based surgical skills learning (WSSL) for basic surgical skill training with promising feedback from a group of final year medical students. 20 In light of the aforesaid benefits, it is envisaged that telehealth will gain further momentum and become a new norm of interaction between healthcare professionals and patients. the patient agrees to be treated, whether or not there has been an encounter in person between the physician (or other appropriately supervised health care practitioner) and patient".…”
Section: The Development Of Telehealth Surgical Practicementioning
confidence: 99%